The Effect of Internal and External Factors on Preventive Reproductive Health Behaviors in Adolescents, in Banjarmasin, Kalimantan - Azura Arisa; RB Soemanto; Setyo Sri Rahardjo (Journal of Health Promotion and Behavior, 2017)
Background: Many adolescents had engaged in unhealthy sexual behavior that can result in unintended health outcomes. In theory, the adolescent sexual behavior is influenced by a complex set of interactions between biology, genetics, individual perception, personality characteristics, and sociocultural norms and values. This study aimed to determine the influence of internal and external factors on preventive reproductive health behavior in adolescents, in Banjarmasin, Kalimantan, using Health Belief Model.Subjects and Method: This was an analytic observational study with the cross-sectional design. The study was conducted at 10 senior high schools in Banjarmasin, Kalimantan. A total sample of 200 grade XI students was selected for this study by proportional stratified random sampling. The dependent variable was preventive reproductive health behavior. The independent variables were perceived susceptibility, perceived seriousness, perceived threat, perceived benefit, perceived barrier, self-efficacy, the role of parents, peer role, and information access. The data were collected by questionnaire and analyzed by path analysis. Results: The strong role of parents (b=0.05; SE= 0.01; p<0.001), perceived benefit (b=0.06; SE= 0.02; p=0.006), perceived threat (b=0.10; SE= 0.02; p<0.001), self-efficacy (b=0.13; SE= 0.01; p<0.001), and peer role (b=0.06; SE= 0.01; p<0.001) positively affected preventive reproductive health behavior. Perceived barrier (b= -0.03; SE= 0.01; p=0.026) negatively affected preventive reproductive health behavior. Perceived threat increased with increasing role of parents (b=0.05; SE= 0.02; p= 0.059), perceived susceptibility (b=0.21; SE= 0.05; p<0.001), perceived seriousness (b=0.10; SE= 0.04; p= 0.015), and self efficacy (b= 0.13; SE= 0.06; p= 0.040). Perceived barrier decreased with improving access of information (b=-0.16; SE= 0.05; p= 0.004). Perceived benefit increased with improving access of information (b=0.09; SE= 0.04; p= 0.030) and perceived susceptibility (b=0.20; SE= 0.06; p= 0.002). Perceived susceptibility (b=0.13; SE= 0.04; p= 0.004), perceived seriousness (b=0.10; SE= 0.05; p= 0.057), and self efficacy (b=0.09; SE= 0.03; p= 0.006) increased with access of information. Self efficacy increased with stronger role of parents (b=0.06; SE= 0.02; p= 0.018), and peer role (b=0.07; SE= 0.04; p= 0.062).Conclusion: Preventive reproductive health behavior among adolescents is affected by the role of parents, perceived of threat, self-efficacy, peer role, perceived of benefit, and perceived of a barrier. Health belief model can predict health preventive behavior.Keywords: Preventive behavior, reproductive health, health belief model, internal and external factorsCorrespondence: Azura Arisa, Masters Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: azura.syakura@gmail.com.Journal of Health Promotion and Behavior (2017), 2(4): 350-358https://doi.org/10.26911/thejhpb.2017.02.04.07